Evaluating Imaging Biomarkers of Acquired Resistance to Targeted EGFR Therapy in Xenograft Models of Human Head and Neck Squamous Cell Carcinoma - Baker, Lauren C. J.; Sikka, Arti; Price, Jonathan M.; Boult, Jessica K. R.; Lepicard, Elise Y.; Box, Gary; Jamin, Yann; Spinks, Terry J.; Kramer-Marek, Gabriela; Leach, Martin O.; Eccles, Suzanne A.; Box, Carol; et al. (Frontiers in Oncology, 2018)
Background: Overexpression of EGFR is a negative prognostic factor in head and neck squamous cell carcinoma (HNSCC). Patients with HNSCC who respond to EGFR-targeted tyrosine kinase inhibitors (TKIs) eventually develop acquired resistance. Strategies to identify HNSCC patients likely to benefit from EGFR-targeted therapies, together with biomarkers of treatment response, would have clinical value. Methods: Functional MRI and 18F-FDG PET were used to visualise and quantify imaging biomarkers associated with drug response within size-matched EGFR TKI-resistant CAL 27 (CALR) and sensitive (CALS) HNSCC xenografts in vivo, and pathological correlates sought. Results: Intrinsic susceptibility, oxygen-enhanced and dynamic contrast-enhanced MRI revealed significantly slower baseline R2*, lower hyperoxia-induced ΔR2* and volume transfer constant Ktrans in the CALR tumours which were associated with significantly lower Hoechst 33342 uptake and greater pimonidazole-adduct formation. There was no difference in oxygen-induced ΔR1 or water diffusivity between the CALR and CALS xenografts. PET revealed significantly higher relative uptake of 18F-FDG in the CALR cohort which was associated with significantly greater Glut-1 expression. Conclusion: CALR xenografts established from HNSCC cells resistant to EGFR TKIs are more hypoxic, poorly perfused and glycolytic than sensitive CALS tumours. MRI combined with PET can be used to non-invasively assess HNSCC response/resistance to EGFR inhibition.